1998
DOI: 10.1038/31948
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor α4 subunit suppression prevents withdrawal properties of an endogenous steroid

Abstract: The hormone progesterone is readily converted to 3alpha-OH-5alpha-pregnan-20-one (3alpha,5alpha-THP) in the brains of males and females. In the brain, 3alpha,5alpha-THP acts like a sedative, decreasing anxiety and reducing seizure activity, by enhancing the function of GABA (gamma-aminobutyric acid), the brain's major inhibitory neurotransmitter. Symptoms of premenstrual syndrome (PMS), such as anxiety and seizure susceptibility, are associated with sharp declines in circulating levels of progesterone and, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
346
1
6

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 535 publications
(389 citation statements)
references
References 26 publications
36
346
1
6
Order By: Relevance
“…Our results showing that the α4 subtype confers a very rapid deactivation rate are also consistent with several neuronal studies in which pathological conditions of hyperexcitability cause an increase in the relative expression of the α4 subunit and a more rapid IPSC decay rate (Smith et al, 1998;Follesa et al, 2004). Again, the change in kinetic properties could be prevented by reducing expression of the α4 subunit (Smith et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results showing that the α4 subtype confers a very rapid deactivation rate are also consistent with several neuronal studies in which pathological conditions of hyperexcitability cause an increase in the relative expression of the α4 subunit and a more rapid IPSC decay rate (Smith et al, 1998;Follesa et al, 2004). Again, the change in kinetic properties could be prevented by reducing expression of the α4 subunit (Smith et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…This pattern is observed in models of hyperexcitability, in which faster IPSC decay rates are associated with an increased seizure susceptibility (Smith et al, 1998). The increase in seizure activity could be reduced by decreasing α4 subunit expression (Smith et al, 1998) or by increasing α1 subunit expression (Raol et al, 2006). Our results suggest that either of these changes in subunit expression would slow the deactivation rate.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The work of Smith and her colleagues has demonstrated that neurosteroid withdrawal results in a state of anxiety and to a relative insensitivity to the anxiolytic effects of benzodiazepines and that these effects appear to be mediated by an increase in the expression of the α4-containing GABA A receptor subunit in brain (Smith et al, 1998a(Smith et al, , 1998b(Smith et al, , 2006. Recently, Smith et al (2006), examined withdrawal from naturally occurring high nocturnal concentrations of allopregnanolone in mice via the administration of finasteride for 3 days.…”
Section: The Neurosteroid Withdrawal Hypothesis In Pmddmentioning
confidence: 99%
“…[11][12][13] This neurosteroid potentiates the inhibitory actions of g-aminobutyric acid (GABA) by modulation of the GABA A receptor. 14 Consistent with this GABAergic mechanism, progesterone and allopregnanolone administration usually produce an anxiolytic effect 11,13 by the action on the amygdala.…”
Section: Introductionmentioning
confidence: 99%